The ties that divide : ethnic politics, foreign policy, and international conflict - Saideman, Stephen M. (Columbia University Press, 2001)
Ethnic conflicts have created crises within NATO and between NATO and Russia, produced massive flows of refugees, destabilized neighboring countries, and increased the risk of nuclear war between Pakistan and India. Interventions have cost the United S.